DAILY PHYSICAL ACTIVITY IN CHILDREN ENROLLED IN EXTRACURRICULAR ACTIVITY - Leite, Marlon Magnon Valdevino [UNESP]; Barela, Ana Maria Forti; Barela, José Angelo [UNESP] (Universidade Estadual de Maringa, 2022)
This study aimed to verify and compare the physical activity practices of children enrolled and non-enrolled on different days of week in a specific program offered at school. Seventy-eight children comprised two groups: children with extra physical activity (EPA; n=39; 15 females and 24 males; age: 9.2±0.8 years) and those with no involvement in extra physical activity (NPA; n=39; 21 females and 18 males; age: 9.0±0.4 years). To infer caloric expenditure, number of steps per day, and total distance traveled, children were monitored with pedometers during three nonconsecutive days: a day with a physical education class at school, a normal activity weekday, and a weekend day. Children enrolled in extra activities at school presented higher levels of caloric expenditure (EPA=132±61, NPA=61±25), performed more steps per day (EPA=7742±2473, NPA=5245±2306) and traveled longer distances (EPA=4201±1318, NPA=2799±1269), with boys (calories=154.1±91.6; steps=9763±3804; traveled distance=5114±2205) more active than girls (calories=94.4±46.7; steps=6691±2394; traveled distance=3726±1387). In the extracurricular physical activity day, children expended more calories (155.8±88.3), performed mores steps (10133±3724) and traveled longer distance (5442±2118) than in the physical education day (calories=127.2±79.3; steps=8409±3283; traveled distance=4478±1864) and in the weekend (calories=96.8±58.8; steps=6493±2687; traveled distance=3500±1466). Extracurricular physical activity at school leads to an increase of physical activity of boys and girls, even on days when the extracurricular activity is not offered.
ATIVIDADE FÍSICA DIÁRIA EM CRIANÇAS PARTICIPANTES DE ATIVIDADE EXTRECURRICULAR
Keywords: active life; children; extracurricular physical activity; Physical activity